The Influence of Good Corporate Governance on Financial Performance in Indonesian Islamic Banking - Dhea Triasdinda; Rismawati; Andika Rusli (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study examines the impact of Good Corporate Governance (GCG) on the financial performance of Sharia banking in Indonesia Tbk. Analyzed GCG variables include the Board of Commissioners, Board of Directors, Independent Commissioners, Sharia Supervisory Board, and Audit Committee. Using a quantitative method with multiple linear regression analysis, the study employs secondary data from annual reports of Sharia banking in Indonesia Tbk. Normality tests were conducted using the One-Sample Kolmogorov-Smirnov test, while heteroscedasticity tests were performed using a scatterplot of residuals against standardized predicted values.Results indicate that none of the independent variables significantly impact financial performance, with p-values well above 0.05. Additionally, the F-test (ANOVA) shows that the independent variables collectively do not significantly impact financial performance, with an F value of 0.243 and a p-value of 0.939. The very low coefficient of determination (R²) of 0.048 suggests that the regression model explains only 4.8% of the variation in financial performance.The implementation of GCG principles at Bank Muamalat Syariah Tbk has not effectively improved financial performance. Therefore, evaluation and improvement of GCG implementation are needed, along with consideration of other factors potentially influencing financial performance. Recommended measures include enhancing the capacity of the Board of Commissioners and Board of Directors, optimizing the role of Independent Commissioners, and increasing the effectiveness of the Sharia Supervisory Board and Audit Committee to improve the bank's financial performance.